2020
DOI: 10.1016/j.precisioneng.2020.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Simple method to determine linearity deviations of topography measuring instruments with a large range axial scanning system

Abstract: The use of areal characterization of surface texture with high accuracy in a quality control process requires reliability. Therefore, regular inspection of the measurement systems is needed. Important metrological features of a measurement system in dimensional metrology are the amplification factor and linearity. This paper presents a simple method for characterizing the axial scanning system of areal topography measuring instruments with little expense and effort, well suited for industrial routine calibrati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Hence, for the measurements performed here the impact of sensor drift was considered negligible on the calibration measurement. The calibration dataset was formed following an existing method [15]; this reduces the need for accurate positioning stages, creating an absolute scale through self comparison against a single calibrated material measure as shown in the following procedure:…”
Section: Methods 2: Step Heightmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, for the measurements performed here the impact of sensor drift was considered negligible on the calibration measurement. The calibration dataset was formed following an existing method [15]; this reduces the need for accurate positioning stages, creating an absolute scale through self comparison against a single calibrated material measure as shown in the following procedure:…”
Section: Methods 2: Step Heightmentioning
confidence: 99%
“…The calibration of sensor operating characteristics should be completed at regular intervals as determined by the measurement context, hence such a calibration regime should be efficient, robust, inexpensive and simple to implement. The literature has shown that such a regime can potentially be achieved through the use of multiple step heights [14] and across a user defined measurement volume [15]. However, the introduction of an additional scanning axis into the calibration procedure increases the impact of the mechanical system on the measurement and increases the time required for calibration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The measured groove depth using the standardized procedure is largely independent of noise and optical effects near the edges. The definition was taken as a basis for extension to 3D topographies by extending the line segments to areas in the calibration standard ISO 25178-700 6.7.4., based on research reported in the scientific literature [13,14].…”
Section: Data Analysis Proceduresmentioning
confidence: 99%
“…A relatively simple procedure to determine the amplification coefficient and linearity deviation for long z-axis range instruments has been recently reported and will likely be included in ISO 25178 part 700 [56]. The procedure employs a material measure containing a number of step heights (positive or negative) and stitches together segments of the response function.…”
Section: Linearity Deviation: Maximum Local Difference Between the Li...mentioning
confidence: 99%